2019
DOI: 10.3390/nu11010177
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Intake by Age, Gender, and Pregnancy Status in the United States: National Health and Nutrition Examination Survey 2003–2014

Abstract: Despite the importance of n-3 fatty acids for health, intakes remain below recommended levels. The objective of this study was to provide an updated assessment of fish and n-3 fatty acid intake (i.e., eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and EPA+DHA) in the United States using the 2003–2014 National Health and Nutrition Examination Survey (NHANES) data (n = 45,347)). Over this survey period, toddlers, children, and adolescents (aged 1–19) had significantly lower n-3 fatty acid intake (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 36 publications
5
76
0
Order By: Relevance
“…Even when accounting for DPA intake, the total daily long‐chain n‐3 fatty acid intake (defined as EPA + DPA + DHA) of the majority of the US population is well below the ~250–500 mg/day amount estimated to be provided by the amount of fish/seafood consumption recommended by the AHA (Arnett et al, ; Rimm et al, ) and the 2015–2020 DGA (U.S. Department of Health and Human Services and U.S. Department of Agriculture, ). Similar to previous findings for EPA and DHA in this population (Thompson et al, ), DPA intake was lower in women and younger age groups (<19 years), even when adjusting for differences in caloric needs between age groups. This pattern of DPA intake was also found in Norway (Johansson et al, ) and similar trends have been reported for EPA and DHA (Papanikolaou et al, ; Richter et al, ; Thompson et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Even when accounting for DPA intake, the total daily long‐chain n‐3 fatty acid intake (defined as EPA + DPA + DHA) of the majority of the US population is well below the ~250–500 mg/day amount estimated to be provided by the amount of fish/seafood consumption recommended by the AHA (Arnett et al, ; Rimm et al, ) and the 2015–2020 DGA (U.S. Department of Health and Human Services and U.S. Department of Agriculture, ). Similar to previous findings for EPA and DHA in this population (Thompson et al, ), DPA intake was lower in women and younger age groups (<19 years), even when adjusting for differences in caloric needs between age groups. This pattern of DPA intake was also found in Norway (Johansson et al, ) and similar trends have been reported for EPA and DHA (Papanikolaou et al, ; Richter et al, ; Thompson et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous findings for EPA and DHA in this population (Thompson et al, ), DPA intake was lower in women and younger age groups (<19 years), even when adjusting for differences in caloric needs between age groups. This pattern of DPA intake was also found in Norway (Johansson et al, ) and similar trends have been reported for EPA and DHA (Papanikolaou et al, ; Richter et al, ; Thompson et al, ). These differences may have implications for dietary recommendations and should be further explored.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A recent worldwide survey of plasma and erythrocyte EPA and DHA content reported a widespread dietary inadequacy, particularly in Western societies [95]. An analysis of NHANES 2003-2014 dietary intake and supplement data found pregnant women had a mean intake of EPA of 33.1 mg (SE = 4.1 mg) and DHA of 67.5 mg (SE = 11.8 mg) per day, and that 7.3% of pregnant women reported taking an EPA or DHA-containing supplement [96]. An analysis by Zhang, et al, (2018) looked at the 2001-2014 NHANES data and found 94.48% of pregnant women were not meeting the 2015-2020 Dietary Guidelines for American's (DGA) of 250 mg of EPA and DHA per day [97].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%